Frailty Index associates with GRIN2B in two representative samples from the United States and the United Kingdom. - Krisztina Mekli; Adam Stevens; Alan D Marshall; Thalida E Arpawong; Drystan F Phillips; Gindo Tampubolon; Jinkook Lee; Carol A Prescott; James Y Nazroo; Neil Pendleton (PLoS ONE, 2018)
The concept of frailty has been used in the clinical and research field for more than two decades. It is usually described as a clinical state of heightened vulnerability to poor resolution of homeostasis after a stressor event, which thereby increases the risk of adverse outcomes, including falls, delirium, disability and mortality. Here we report the results of the first genome-wide association scan and comparative gene ontology analyses where we aimed to identify genes and pathways associated with the deficit model of frailty. We used a discovery-replication design with two independent, nationally representative samples of older adults. The square-root transformed Frailty Index (FI) was the outcome variable, and age and sex were included as covariates. We report one hit exceeding genome-wide significance: the rs6765037 A allele was significantly associated with a decrease in the square-root transformed FI score in the Discovery sample (beta = -0.01958, p = 2.14E-08), without confirmation in the Replication sample. We also report a nominal replication: the rs7134291 A allele was significantly associated with a decrease in the square-root transformed FI score (Discovery sample: beta = -0.01021, p = 1.85E-06, Replication sample: beta = -0.005013, p = 0.03433). These hits represent the KBTBD12 and the GRIN2B genes, respectively. Comparative gene ontology analysis identified the pathways 'Neuropathic pain signalling in dorsal horn neurons' and the 'GPCR-Mediated Nutrient Sensing in Enteroendocrine Cells', exceeding the p = 0.01 significance in both samples, although this result does not survive correction for multiple testing. Considering the crucial role of GRIN2B in brain development, synaptic plasticity and cognition, this gene appears to be a potential candidate to play a role in frailty. In conclusion, we conducted genome-wide association scan and pathway analyses and have identified genes and pathways with potential roles in frailty. However, frailty is a complex condition. Therefore, further research is required to confirm our results and more thoroughly identify relevant biological mechanisms.